OsBSK1-2, an Orthologous of AtBSK1, Is Involved in Rice Immunity - Wang, Jing; Shi, Hui; Zhou, Lian; Peng, Chunfang; Liu, Dingyou; Zhou, Xiaogang; Wu, Wenguan; Yin, Junjie; Qin, Hai; Ma, Weiwei; He, Min; Li, Weitao; et al. (Frontiers in Plant Science, 2017)
The brassinosteroid-SIGNALLING KINASE (BSK) belongs to the receptor-like cytoplasmic kinase XII subgroup. BSK1 regulates development and immunity in Arabidopsis. However, the function of rice (Oryza sativa) BSK1 is largely unknown. Here, we report that the expression level of OsBSK1-2 is induced after a chitin or fagellin22 (flg22) treatment. Silencing OsBSK1-2 in rice results in compromised responses to chitin- or flg22-triggered immunity and resistance to Magnaporthe oryzae, but does not alter the plant’s architecture nor reduce plant responses to brassinosteroid signaling. Our study reveals that OsBSK1-2 functions as a major regulator in rice plant immunity.